Knowledge accumulation techniques in MINEX-an electronic field guide to rocks and minerals - Nagel, J.; Meech, J.A. (1995 IEEE International Conference on Systems, Man and Cybernetics, 1995)
Development of an expert system to teach qualitative mineralogy is presented. The system is designed to help a user learn the subject and not rely on the program as a "black-box". A consultation session attempts to mimic the dialogue that might occur between an expert mineralogist and a novice examining a mineral specimen. Inputs such as unique properties, crystal characteristics, luster, color, streak, hardness, S.G. and cleavage are used to decide if the mineral is indeed, the one the pupil has suggested. The paper describes the method used to accumulate heuristic observations even when data are extremely uncertain.